The Students’ Perception Toward the Use of Smartphones in Learning English at MAN Sidenreng Rappang - Maming, Khadijah; Sudarmanto; Mimi Kartika (Universitas Cokroaminoto Palopo, 2023)
Technology and education are two things that cannot be separated until now. Especially when the pandemic outbreak hit which required the education world to implement an online learning system, smartphones became one of the choices for learning media. However, researchers found a phenomenon that occurred in MAN Sidenreng Rappang after the covid-19 pandemic, where students could use smartphones in the learning process in the classroom. This study aims to determine how students' perceptions of smartphone use in learning English at MAN Sidenreng Rappang. Participants in the study consisted of seven students from twelfth grade. In addition, this study used observation, interview, and documentation techniques to obtain data. From the findings, researchers found that smartphones can be used as one of the learning media in accordance with the results of research that shows a positive impact related to the use of smartphones in learning English in the classroom, such as making learning more fun, making it easier for students to access learning materials. Smartphones also provide various features and applications that help in the learning process, such as easier assignment collection, helping the translation process, and various applications that can support the learning process. The use of smartphones also improves students' skills, especially in improving vocabulary, speaking, and listening skills. In addition, the use of smartphones also motivates students to learn. But from the findings, researchers also found several obstacles faced by students while using smartphones, such as disruption of learning focus, data packages, and poor internet connection.